ANTI-MICROBIAL ACTIVITY OF IRRIGANTS ON ENTEROCOCCUS FAECALIS: IN-VITRO ANALYSIS - Choudhari, Sahil; S, Chandana; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
INTRODUCTION: The contribution of microorganisms to the development of pulpal and periapical disease has been well documented. The bacteria associated with primary endodontic infections are mixed but are predominantly gram-negative anaerobic rods, whereas the bacteria associated with secondary infection comprise only one or a few bacterial species-the most important of which is Enterococcus faecalis. The purpose of this study was to compare and evaluate the antimicrobial efficacy of ChloroQuick with Sodium Hypochlorite and 2% Chlorhexidine gluconate on E.faecalis. MATERIALS AND METHODS: Thirty extracted human lower bicuspids with a single root canal, checked by radiographs were selected. E. faecalis suspensions were injected into the canals of all teeth using sterile insulin syringes under aseptic conditions. In group 1, 10 root canals were irrigated with 0.9% NaOCl In group 2, 10 root canals were irrigated with ChloroQuick. In group 3, 10 root canals were irrigated with 2% CHX. Sterile paper points were selected to sample the bacteria from root canals after cleaning and shaping the root canal. The paper points were left in the canal for 1 minute and the samples were transported into plates containing TSA with 5% sheep blood and placed in an incubator at 37 degree celsius for 48 hours. The samples were retrieved from the incubator after 48 hours to be evaluated bacteriologically as to the presence of microorganisms and observation of the colonies formed. RESULTS: Bacterial growth was seen only in one sample of ChloroQuick, but in 3 of CHX group and 2 of NaOCl group. Chi-Square test showed no statistical difference between groups. CONCLUSION: Based on the results of this study, it seems that all three solutions have acceptable antimicrobial effect on E. faecalis.